THE SIMILARITY OF THE MEDINA CHARTER AND THE INDONESIAN CONSTITUTION IN HUMAN RIGHT’S PROTECTION - Faiq Tobroni (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
The movement that wants to make an Islamic constitution still threatens Indonesia. This movement is exacerbated by the misunderstanding that the Medina Charter was proof of the obligation for Muslims to establish an Islamic state as was done by the Prophet Muhammad. In fact, the Medina Charter regulates more about the protection of human rights (HAM) for every citizen regardless of religious background.This study aims to examine the position of the Medina charter as an argument for the establishment of the state and the similarity between the Indonesian constitution and the spirit of protecting human rights in the Medina charter. This research is a literature review by examining classical and modern references relevant to the establishment of the state and the Medina Charter. The finding in this research is that the Medina charter is a legal product at the time of the Prophet Muhammad (pbuh). Muslims are not obliged to establish a form of Islamic State and a constitution that is exactly the same as what was done by the Prophet Muhammad (pbuh). In substance, the Medina Charter is a symbol of peace, tolerance and moderation. Thus, philosophically, the spirit of the Medina charter has been embodied in the Indonesian constitution which has prioritized the peace and welfare of the people. The implication of this finding is that there is no necessity for the establishment of an Islamic State. Without declaring an Islamic constitution, the 1945 Constitution accommodates the spirit of protecting human rights which is in line with the Medina charter.